2014
DOI: 10.1093/infdis/jiu196
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Multivalent, Single-Domain Antibody Targeting TcdA and TcdB Prevents Fulminant Clostridium difficile Infection in Mice

Abstract: The incidence of Clostridium difficile infection (CDI) and associated mortality have increased rapidly worldwide in recent years. Therefore, it is critical to develop new therapies for CDI. In this study, we generated a novel, potently neutralizing, tetravalent, and bispecific antibody composed of 2 heavy-chain-only VH (VHH) binding domains against both TcdA and TcdB (designated "ABA") that reverses fulminant CDI in mice infected with an epidemic 027 strain after a single injection of the antibody. We demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
123
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 96 publications
(128 citation statements)
references
References 47 publications
5
123
0
Order By: Relevance
“…In both mouse and hamster infection models of CDI, preventing infection-associated mortality is seen as an important metric of vaccine efficacy (12,13,22,23,(58)(59)(60)(61)(62)(63)(64)(65)(66). Upon challenging pRBD-NQ-immunized animals with a lethal dose of spores, we observed 90% and 50% protection against homologous and heterologous strains, respectively.…”
Section: Discussionmentioning
confidence: 87%
“…In both mouse and hamster infection models of CDI, preventing infection-associated mortality is seen as an important metric of vaccine efficacy (12,13,22,23,(58)(59)(60)(61)(62)(63)(64)(65)(66). Upon challenging pRBD-NQ-immunized animals with a lethal dose of spores, we observed 90% and 50% protection against homologous and heterologous strains, respectively.…”
Section: Discussionmentioning
confidence: 87%
“…Heterodimeric VNAs Protect against Anthrax Toxin and Spore Infection in Mice-Linking toxin-neutralizing VHHs into heteromultimeric VNAs has been found to improve toxin affinity and, more importantly, to substantially improve in vivo antitoxin efficacy (11)(12)(13)16). A heterodimeric VNA (VNA2-PA) consisting of the two potent neutralizing VHHs, JIK-B8 and JKH-C7, separated by a short unstructured peptide, was expressed and purified (amino acid sequence shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…32 and 6). We have found that VHH heteromultimer VNAs possess additional potential therapeutic advantages over conventional mAb products such as 1) the option to co-administer an anti-tag effector antibody that binds multiple tags on the VNAs (11,13) to promote antibody Fc effector functions such as serum clearance (33), 2) the ability to target multiple toxins with one biomolecule (12,16), and 3) the use of VNA gene therapy as an effective means to provide prolonged antitoxin protection (34,35). Simple addition of an albumin binding peptide (34,36) can dramatically improve the serum stability of VNAs (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…V H Hs have been reported in the treatment of toxin-mediated disease (48,49). V H Hs against the two C. difficile toxins have also been generated which possessed toxin-neutralizing activity (42,50) and potent therapeutic efficacy against fulminant C. difficile infection (51).…”
mentioning
confidence: 99%